Ulcerative Colitis in a COVID-19 Patient: A Case Report - Aydın, Muhammet Fatih; Taşdemir, Hamit (Turkish Journal of Gastroenterology, 2021)
COVID-19 pneumonia is a global viral disease and has been classified as a pandemic by the World Health Organization. The coronavirus that causes it can remain in the stool for some time in some infected patients, even after recovery from COVID-19 pneumonia. Studies have increasingly reported the involvement of other organs, including the gastrointestinal system, in addition to the respiratory symptoms of COVID-19. Ulcerative colitis is an inflammatory bowel disease with an unknown cause; emerging data suggest that the gastrointestinal system may be influenced by COVID-19 via the expression of ACE-2, but data on the association between COVID-19 and inflammatory bowel diseases, including ulcerative colitis, are lacking. In this report, we describe a case of ulcerative colitis diagnosed in a 50-year-old male patient who presented with complaints of bloody diarrhea and abdominal pain following the completion of treatment for COVID-19 pneumonia. It is possible for the novel coronavirus to trigger ulcerative colitis. Patients presenting with gastrointestinal complaints should also be evaluated for COVID-19.